Surufatinib combined with photodynamic therapy induces ferroptosis to inhibit cholangiocarcinoma in vitro and in tumor models - Huang, Yun-Peng; Wang, Yong-Xiang; Zhou, Hui; Liu, Zhong-Tao; Zhang, Zi-Jian; Xiong, Li; Zou, Heng; Wen, Yu (Frontiers in Pharmacology, 2024)
The curative effect of single therapy for advanced cholangiocarcinoma (CCA) is poor, thus investigating combined treatment strategies holds promise for improving prognosis. Surufatinib (SUR) is a novel multikinase inhibitor that has been confirmed to prolong survival of patients with advanced CCA. Photodynamic therapy (PDT) can also ablate advanced CCA and relieve biliary obstruction. In this study, we explored the anti-CCA effect of SUR combined with PDT, and explored the underlying mechanism.We found that SUR could effectively inhibit the abilities of proliferation, migration and metastasis in CCA cells (HUCCT-1, RBE). The ability of SUR to inhibit CCA was also confirmed by the HUCCT-1 cell xenograft model in Balb/c nude mice and CCA patientderived organoids. SUR combined with PDT can significantly enhance the inhibitory effect on CCA, and can be alleviated by two ferroptosis inhibitors (Ferrostatin-1, Deferoxamine). By detecting the level of reactive oxygen species, lipid peroxides, malondialdehyde and glutathione, we further confirmed that SUR combined with PDT can inhibit CCA cells by inducing ferroptosis. Glutathione peroxidase 4 (GPX4) belongs to the glutathione peroxidase family and is mainly responsible for the metabolism of intracellular hydrogen peroxide. GPX4 inhibits ferroptosis by reducing cytotoxic lipid peroxides (L-OOH) to the corresponding alcohols (L-OH). Acyl-CoA synthetase long-chain family member 4 (ACSL4) is a member of the long-chain fatty acid coenzyme a synthetase family and is mainly involved in the biosynthesis and catabolism of fatty acids. ACSL4 induces ferroptosis by promoting the accumulation of lipid peroxides. Both SUR and PDT can induce ferroptosis by promoting ACSL4 and inhibiting GPX4. The regulation effect is found to be more significant in combined treatment group. In conclusion, SUR combined with PDT exerted an anti-CCA effect by inducing ferroptosis. Combination therapy provides a new idea for the clinical treatment of CCA.